A prospective randomized trial of povidone-iodine suppository before transrectal ultrasonography-guided prostate biopsy. Issue 12 (March 2019) - Ryu, Hoyoung; Song, Sang Hun; Lee, Sang Eun; Song, Kyoung-Ho; Lee, Sangchul
Abstract: Objectives: To investigate a way to reduce infectious complication after transrectal ultrasonography-guided prostate biopsy (TRUS-Bx), we planned a randomized trial to determine whether the use of the povidone-iodine suppository is effective in preventing infectious complications. Methods: This study prospectively assessed 250 patients who underwent TRUS-Bx during December 2014 and May 2016. Clinical questionnaire responses and safety were evaluated. Povidone-iodine suppository after glycerin enema was performed 1 to 2 hours before TRUS-Bx. Both groups received the prophylactic antibiotics (ceftriaxone 2.0 g) 30 to 60 minutes before TRUS-Bx. No antibiotics were prescribed after TRUS-Bx. Results: The 120 were assigned in the treatment group using povidone-iodine suppository and 130 were assigned in the control group. There was no significant difference of clinicopathologic features including age, prostate-specific antigen and cancer detection rate in both groups ( P  > .05). No infectious and non-infectious complications were reported in both groups. Povidone-iodine suppository-related side effects were not reported. No significant differences in international prostate symptom score, sexual health inventory for men score, and European Organization for Research and Treatment of Cancer Quality of Life questionnaire scores were found between the 2 groups ( P  > .05). No changes in each questionnaire scores between before and after TRUS-Bx were observed. Conclusions: Despite satisfying the predefined sample size, we could not prove the hypothesis that the use of povidone-iodine suppositories after TRUS-Bx would reduce infectious complications. A large-scale, multicenter, prospective study is needed to fully evaluate the clinical efficacy and safety of povidone-iodine suppository prior to TRUS-Bx.